2016
DOI: 10.1371/journal.pone.0164298
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Synthase 1 Is Essential for Male Fertility in Mice

Abstract: Sphingolipids and the derived gangliosides have critical functions in spermatogenesis, thus mutations in genes involved in sphingolipid biogenesis are often associated with male infertility. We have generated a transgenic mouse line carrying an insertion in the sphingomyelin synthase gene Sms1, the enzyme which generates sphingomyelin species in the Golgi apparatus. We describe the spermatogenesis defect of Sms1-/- mice, which is characterized by sloughing of spermatocytes and spermatids, causing progressive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 70 publications
1
17
0
Order By: Relevance
“… 105 In the testis of SMS1-KO mice, the levels of SM with several long chain unsaturated PC and lyso-PC were reduced, resulting in male fertility. 106 In our study, the levels of very long chain SMs (C24:1 and C24:0) in the testis were increased, and brain SM levels were significantly decreased in SMS1-KO mice ( Table 1 ). 96 Xue et al 107 have reported that SMS2 deficiency also resulted in decreased SM levels in the mouse brain.…”
Section: Ceramide/sm Balance and Sphingolipid Metabolism In Sms-ko MIsupporting
confidence: 55%
See 1 more Smart Citation
“… 105 In the testis of SMS1-KO mice, the levels of SM with several long chain unsaturated PC and lyso-PC were reduced, resulting in male fertility. 106 In our study, the levels of very long chain SMs (C24:1 and C24:0) in the testis were increased, and brain SM levels were significantly decreased in SMS1-KO mice ( Table 1 ). 96 Xue et al 107 have reported that SMS2 deficiency also resulted in decreased SM levels in the mouse brain.…”
Section: Ceramide/sm Balance and Sphingolipid Metabolism In Sms-ko MIsupporting
confidence: 55%
“…In addition, a defect in spermatogenesis causing male infertility was found in SMS1-KO male mice. 106 Alterations in SM metabolism by SMS1 deficiency reduced not only SM, but also polyunsaturated PC and lyso-PC. Dysfunction and leakage of blood-testis barrier, which is based on cell-cell junctions and maintains the microenvironment for spermatogenesis at the seminiferous tubule, 112 occurred in SMS1-KO mice due to change in polyunsaturated fatty acid (PUFA) homeostasis.…”
Section: Phenotypes Of Smss-ko Mice In Disease Modelsmentioning
confidence: 99%
“…Thus, although the lowest SMS1 expression was about 57%, the highest expression measured in glioma patients (Figure S8), siSMS1 caused a reduction to 10% of the control SMS1 expression in vitro, potentially compromising GBM cell survival. This premise is supported by the fact that SMS1 KO mice show deteriorated growth and male infertility, and they are born in a lower Mendelian ratio [36,37], which indicates the relevance of SMS1 expression during development.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, our results suggested that SMS2 may play some role(s) in spermatogenesis. In fact, Wittmann et al also showed similar results for SMS1 in mice, wherein SMS1 plays a wider role in testis polyunsaturated fatty acid homeostasis and in male fertility [ 21 ]. Moreover, when we tested the SMS2 expression in sperm cells, we were able to show that the SMS2 was located mainly on the head and tail of sperm cells.…”
Section: Discussionmentioning
confidence: 90%
“…In detail, SM can influence the rate of capacitation by slowing the loss of sterols [ 19 ]. Moreover, Lee et al and Wittmann et al suggested that SMS may play a crucial role in sloughing of spermatocytes and spermatids, causing progressive infertility of male homozygotes, acrosome formation, and plasma membrane restructuring from late round spermatids to early elongating spermatids by affecting the lipid metabolism in mice [ 20 , 21 ]. Clearly, SMS are associated with male infertility.…”
Section: Introductionmentioning
confidence: 99%